2021
DOI: 10.3389/fpsyt.2021.766647
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Power Spectral Density and Spindles in PTSD and Their Relationship to Symptom Severity

Abstract: Sleep disturbances are common in post-traumatic stress disorder (PTSD), although which sleep microarchitectural characteristics reliably classify those with and without PTSD remains equivocal. Here, we investigated sleep microarchitectural differences (i.e., spectral power, spindle activity) in trauma-exposed individuals that met (n = 45) or did not meet (n = 52) criteria for PTSD and how these differences relate to post-traumatic and related psychopathological symptoms. Using ecologically-relevant home sleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 73 publications
0
27
0
Order By: Relevance
“…PSD in the range of 0-30 Hz was included in the analysis (e.g. Denis et al, 2021). Separate tests were performed for NREM and REM sleep.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PSD in the range of 0-30 Hz was included in the analysis (e.g. Denis et al, 2021). Separate tests were performed for NREM and REM sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Theta (∼4-7Hz) oscillatory power during REM sleep has been linked to emotional memory processing during sleep in some studies (Kim et al, 2019; Marquis et al, 2017; Nishida et al, 2009; Schäfer et al, 2020; Sopp et al, 2017), though this association has not been found (Davidson et al, 2021). Theta power has been shown to be elevated in trauma-exposed individuals who were resilient to, compared to those diagnosed with, PTSD (Cowdin et al, 2014; though see Denis et al, 2021). Similarly, electroencephalographic spectral power in in the beta frequency range (∼20-30Hz) during sleep has also been shown to be elevated in PTSD compared to those without PTSD (de Boer et al, 2020; Germain et al, 2006; Wang et al, 2020; Woodward et al, 2000), and has been theorized as a marker of hyperarousal (Hall et al, 2007; Krystal et al, 2002; Perlis et al, 2001; Riedner et al, 2016; Spiegelhalder et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In major depression, sleep spindles increase density and shift toward frontal and parietal cortices ( Plante et al, 2013 , Ferrarelli et al, 2019 ). In PTSD, fast sleep spindles increase peak frequencies ( Denis et al, 2021 ). Indeed, we observed a shift of fast spindles toward parietal regions in people discharged from non-ICU and towards anterior areas in people discharged from ICU.…”
Section: Discussionmentioning
confidence: 99%
“…In major depression, sleep spindles have an increased density and distribution over frontal and parietal cortices ( Plante et al, 2013 ). In post-traumatic stress disorder (PTSD), fast sleep spindles apparently increase peak frequencies ( Denis et al, 2021 ). The study of cortical generators of neural activity has further extended our knowledge of the neurophysiology of cognition and sleep.…”
Section: Introductionmentioning
confidence: 99%